Evidence of a small, island-associated population of common bottlenose dolphins in the Mariana Islands - Martien, Karen K.; Hill, Marie C.; Archer, Frederick I.; Baird, Robin W.; Bendlin, Andrea R.; Dolar, Louella; Ligon, Allan D.; Oleson, Erin M.; Robertson, Kelly M.; Woodman, Samuel M.; Ü, Adam C.; Yano, Kymberly M.; et al. (Frontiers in Marine Science, 2024)
Small, island-associated populations of cetaceans have evolved around numerous oceanic islands, likely due to habitat discontinuities between nearshore and offshore waters. However, little is known about the ecology and structure of cetacean populations around the Mariana Islands, a remote archipelago in the western Pacific Ocean. We present sighting, photo-identification, and genetic data collected during twelve years of surveys around these islands that reveal the existence of a small, island-associated population of bottlenose dolphins. Nearly half of the photo-identified individuals were encountered in more than one year. Both haplotypic and nuclear genetic diversity among sampled individuals was low (haplotypic diversity = 0.701, nuclear heterozygosity = 0.658), suggesting low abundance. We used mark-recapture analysis of photo-identification data to estimate